2018
DOI: 10.1136/bmjspcare-2018-001632
|View full text |Cite
|
Sign up to set email alerts
|

The liminal space palliative care volunteers occupy and their roles within it: a qualitative study

Abstract: ObjectivesVolunteers have an important place in palliative care (PC), positively influencing quality of care for seriously ill people and those close to them and providing a link to the community. However, it is not well understood where volunteers fit into PC provision or how to support them adequately. We therefore chose to describe volunteer roles across care settings through the perspective of those closely involved in the care of terminally ill people.MethodsA qualitative study was conducted using both fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 35 publications
(17 reference statements)
3
43
0
3
Order By: Relevance
“…Lower response rates from certain types of volunteers, such as those in nursing homes and community home care, imply possible issues for statistical generalisation and, hence, that results for the particular organisational types should be interpreted with caution. Results nevertheless confirm the findings from a previous organisational study of palliative care volunteering (Vanderstichelen et al, ; Vanderstichelen, Houttekier, et al, ) and are contextualised by previous qualitative studies of volunteering in these settings (Vanderstichelen, Cohen, Van Wesemael, Deliens, & Chambaere, ; Vanderstichelen et al, ), indicating the validity of our current conclusions. Strongly involved volunteers may be overrepresented in these strata.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Lower response rates from certain types of volunteers, such as those in nursing homes and community home care, imply possible issues for statistical generalisation and, hence, that results for the particular organisational types should be interpreted with caution. Results nevertheless confirm the findings from a previous organisational study of palliative care volunteering (Vanderstichelen et al, ; Vanderstichelen, Houttekier, et al, ) and are contextualised by previous qualitative studies of volunteering in these settings (Vanderstichelen, Cohen, Van Wesemael, Deliens, & Chambaere, ; Vanderstichelen et al, ), indicating the validity of our current conclusions. Strongly involved volunteers may be overrepresented in these strata.…”
Section: Discussionsupporting
confidence: 91%
“…Across health services, volunteers collaborated mainly with fellow volunteers, volunteer coordinators, nurses and family caregivers. Dedicated palliative care volunteers collaborated most often and extensively with nurses, confirming previous studies that have shown the importance of nurses to palliative care volunteering (Vanderstichelen, Cohen, et al, ; Vanderstichelen et al, ). Inpatient care service volunteers collaborated more with nurses than extramural care volunteers, however, the latter collaborated more with family caregivers than other volunteers.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Moreover, volunteers provide vital human companionship for patients facing compassionate palliative or end-of-life care without friends or family to support them. [4][5][6][7] This companionship has implications on patient wellness including decreased feelings of loneliness, isolation, depression and anxiety. 8 Volunteers significantly attenuate the cost of hospice care, and they improve standards of care and efficiency by allowing medical professionals to focus on treating the physiological needs of the patients.…”
Section: Medical Volunteers Provide Important Patient-centred Carementioning
confidence: 99%
“…6. Steven Vanderstichelen et al (2018) , “The Liminal Space Palliative Care Volunteers Occupy and Their Roles Within It: A Qualitative Study,” BMJ Support Palliat Care . https://doi.org/10.1136/bmjspcare-2018-001632…”
mentioning
confidence: 99%